3D Hierarchical heterostructures of Bi2W1−xMoxO6 with enhanced oxygen evolution reaction from water under natural sunlight. (9th October 2018) - Kulkarni, Aniruddha K.; Panmand, Rajendra P.; Sethi, Yogesh A.; Kadam, Sunil R.; Patil, Deepak R.; Ghule, Anil V.; Kale, Bharat B.
Abstract : Self-assembled 3D hierarchical Bi2 W1− x Mo x O6 heterostructures with varying x ( x = 0, 0.2, 0.4, 0.6, 0.8 or 1.0) with different morphologies were synthesised via a facile one-pot solvothermal method and their photocatalytic activity towards the oxygen evolution reaction (OER) from water under natural sunlight was tested. Abstract : Self-assembled 3D hierarchical Bi2 W1− x Mo x O6 heterostructures with varying x ( x = 0, 0.2, 0.4, 0.6, 0.8 or 1.0) with different morphologies were synthesised via a facile one-pot solvothermal method and their photocatalytic activity towards the oxygen evolution reaction (OER) from water under natural sunlight was tested. The structural properties of Bi2 W1− x Mo x O6 were studied by the X-ray diffraction (XRD) technique, which showed an orthorhombic Aurivillius layered crystal structure. The microstructural features were examined by FE-SEM and FE-TEM techniques which showed that the morphology of Bi2 WO6 varies with substitution of Mo and each morphological structure grows via the assembly of tiny nanoparticles of size 50 nm. The effective substitution of Mo in Bi2 WO6 extends the optical absorption towards the visible region. The substitution of Mo in place of W was confirmed by X-ray photoelectron spectroscopy. The photocatalytic activities were evaluated by OER under solar light irradiation. The sample Bi2 W0.6 Mo0.4 O6 (S3) shows enhanced photocatalytic activity for OER from aqueous AgNO3 solution (652 μmol h −1 g −1 ) which is higher than for pristine Bi2 MoO6 or Bi2 WO6 photocatalysts. Enhanced photocatalytic activity can be attributed to the extended absorption in the visible light region, which enhances the photocatalytic efficiency of the photocatalysts. More significantly, the 3D intrinsically layered nanosheet structure based morphology, and the unique band structure are beneficial for efficient charge transfer, which enhances the photocatalytic activity. This work demonstrates an effective strategy for developing an active photocatalyst with greater utilization of solar light.